Is it always Wilms' tumor? Localized cystic disease of the kidney in an infant. An extremely rare case report and review of the literature - Christos Kaselas; Charikleia Demiri; Vasilios Mouravas; Eleni Koutra; Kleanthis Anastasiadis; Ioannis Spyridakis (MDPI AG, 2020)
Localized Cystic Disease of the Kidney (LCDK) is an extremely rare benign disease in pediatric population. Although its management is conservative and generally requires no treatment, the unfamiliarity with the disease can expose such patients to misdiagnosis as renal malignancies or uncertainty for proper treatment. We report such a case in an infant and review the current literature.